DEVELOPING INDEPENDENT LEARNING IN PHYSICS EDUCATION BASED ON THE STEM APPROACH - Quchqorov Shohjahon Xazrat o‘g‘li (World Scientific Research Journal, 2025)
The integration of STEM (Science, Technology, Engineering, and Mathematics) education has become a pivotal approach in modernizing teaching methodologies, particularly in physics education. This paper investigates how the STEM approach can effectively foster independent learning skills among physics students in technical higher education institutions. Independent learning is a crucial competency that empowers students to take ownership of their educational journey, develop critical thinking, and solve complex problems autonomously. By embedding STEM principles into physics curricula, educators can promote active engagement, deeper conceptual understanding, and practical application of theoretical knowledge. The study analyzes various pedagogical strategies, including problem-based learning, inquiry-based activities, and the use of interactive digital tools such as simulations and virtual laboratories. These methods encourage students to explore, experiment, and reflect on physical phenomena without constant instructor supervision, thereby enhancing their self-regulation and motivation. Furthermore, the research reviews case studies and practical implementations from technical universities that demonstrate positive outcomes in student performance and independent study habits.